An Oleocanthal-Enriched EVO Oil Extract Induces the ROS Production in Gastric Cancer Cells and Potentiates the Effect of Chemotherapy - Sara Peri; Jessica Ruzzolini; Silvia Urciuoli; Giampaolo Versienti; Alessio Biagioni; Elena Andreucci; Silvia Peppicelli; Francesca Bianchini; Andrea Bottari; Lido Calorini; Chiara Nediani; Lucia Magnelli; et al. (Antioxidants, 2022)
Oleocanthal, a minor polar compound in extra-virgin olive (EVO) oil, contains anticancer properties, which should be encouraged in its use in oncology. Gastric Cancer (GC), a very aggressive human cancer, is often diagnosed at advanced stages, when surgery is substituted or supported by chemotherapy (CT). However, CT frequently fails due to the patient’s resistance to the treatment. Thus, the aim of this study is to verify whether an OC-enriched EVO oil extract fraction (OCF) may be useful in order to overcome a resistance to GC. We evaluated the OCF effects on an AGS gastric adenocarcinoma cell line wild type (AGS wt) and on its subpopulations resistant to 5-fluorouracil (5FUr), Paclitaxel (TAXr) or cisplatin (CISr). We found that a 60 µM dose of the OCF acts on the AGS wt, 5FUr and TAXr, leading to the cell cycle inhibition and to a ROS production, but not on CISr cells. Resistance of CISr to the OCF seems to be due to higher levels of antioxidant-enzymes that can counteract the OCF-induced ROS production. Moreover, using the OCF plus 5-fluorouracil, Paclitaxel or cisplatin, we found a potentiating effect compared with a mono-treatment in all resistant GC cells, including CISr. In conclusion, the use of the OCF in the management of GC has shown very interesting advantages, opening-up the possibility to evaluate the efficacy of the OCF in vivo, as a valid adjuvant in the treatment of resistant GC.